The Saving Order of Science: New Atheist Sam Harris’s Scientism is not Fundamentalism but Affective Attachment to a Salvific Epistemology - Ruper, Stefani (Eidos. A Journal for Philosophy of Culture, 2024)
The New Atheist movement has been called “fundamentalist” in its allegiance to science. While true that New Atheism is remarkable among the various historical formations of atheism for its championing of the sciences, it is not fundamentalist. Where it does share a resemblance to Christian fundamentalism is in their respective attachments to a salvific epistemology either of science or of faith. For New Atheists, science “saves” as it provides order against chaos. This paper focuses on the writings of the New Atheist Sam Harris, drawing attention not just to the ordering function of science generally but also the ways in which Harris deploys science to engulf 1) morality, 2) the Buddhist belief that the self is an illusion, and 3) Buddhist practices of meditation. This study illuminates some affective potencies of science (or other potential epistemologies) as an ordering, and therefore “salvific,” way of navigating the world.